Job Search, Bargaining, and Wage Dynamics - Yamaguchi, Shintaro (Journal of Labor Economics, 2010)
This article constructs and estimates a model of wage bargaining with on‐the‐job search to explore three different components of wages: general human capital, match‐specific capital, and outside options. As the workers find better job opportunities, the current employer has to compete with outside firms to retain them. This between‐firm competition results in wage growth even when productivity remains the same. The model is estimated by a simulated minimum distance estimator and data from the 1979 National Longitudinal Study of Youth. The results indicate that the improved value of the outside option raises wages by 14%–16% in the first 5 years.